Categorical encoding of moving colors during location tracking. (March 2023) - Sun, Mengdan; Xin, Xiaoyang; Ying, Haojiang; Hu, Luming; Zhang, Xuemin
Categorical perception (CP) describes our tendency to perceive the visual world in a categorical manner, suggesting that high-level cognition may affect perception. While most studies are conducted in static visual scenes, Sun and colleagues found CP effects of color in multiple object tracking (MOT). This study used functional magnetic resonance imaging to investigate the neural mechanism behind the categorical effects of color in MOT. Categorical effects were associated with activities in a broad range of brain regions, including both the ventral (V4, middle temporal gyrus) and dorsal pathways (MT + /V5, inferior parietal lobule) of feature processing, as well as frontal regions (middle frontal gyrus, medial superior frontal gyrus). We proposed that these regions are hierarchically organized and responsible for distinct functions. The color-selective V4 encodes color categories, making cross-category colors more discriminable than within-category colors. Meanwhile, the language and/or semantic regions encode the verbal information of the colors. Both visual and nonvisual codes of color categories then modulate the activities of motion-sensitive MT + areas and frontal areas responsible for attentional processes.